A nascent protein labeling strategy disclosed mitochondrial proteomic responses in punicalagin intervened insulin resistance of HepG2 cells. Issue 3 (12th January 2022) - Zhang, Zhengyi; Zeng, Mengqi; Han, Xiao; Hou, Zhanwu; Wang, Zhen; Su, Tian; Zhao, Wei; Liu, Jiankang; Liu, Huadong
Abstract : Insulin Resistance (IR), as a common pathophysiological basis, is closely related to a variety of metabolic diseases, such as obesity and diabetes. Abstract : Insulin resistance (IR), as a common pathophysiological basis, is closely related to a variety of metabolic diseases, such as obesity and diabetes. IR is often accompanied by mitochondrial dysfunction which could be induced by a high fat diet. Punicalagin (PU), a natural compound extracted from pomegranate, could ameliorate palmitate-induced IR. However, the underlying mechanisms are not well known. We propose that understanding the proteomic response of mitochondria may help define the mechanisms of PU in the prevention of IR. Most of the mitochondrial proteins are encoded by nuclear genes and transported from cytoplasm. To distinguish newly incorporated proteins responding to stimuli from pre-existing mitochondrial proteome, nascent proteins in HepG2 cells were pulse labeled by an amino acid analog l -azidohomoalanine. Nascent nuclear encoded mitochondrial proteins were enriched by click reaction followed by mass detection. Our data showed that PU increased nuclear encoded protein incorporation to mitochondria in general though the total protein levels remained immobile. To decipher this phenomenon, we tested the protein and mRNA levels of genes related to mitophagy and mitochondrial biogenesis and found that the mitochondrial turnover was accelerated by PU treatment. By the nascent protein labeling strategy and pathway analysis, we enriched the newly incorporated proteins of mitochondria for responding to PU treatment and found that PU induced nascent protein incorporation into mitochondria and enhanced mitochondrial turnover. These findings demonstrate that PU prevents IR by targeting mitochondria, and thus, is an effective natural nutrient beneficial for mitochondrial turnover.